Particle Size Effect on Powder Packing Properties and Molten Pool Dimensions in Laser Powder Bed Fusion Simulation - Jun Katagiri; Sukeharu Nomoto; Masahiro Kusano; Makoto Watanabe (Journal of Manufacturing and Materials Processing, 2024)
Various defects are produced during the laser powder bed fusion (L-PBF) process, which can affect the quality of the fabricated part. Previous studies have revealed that the defects formed are correlated with molten pool dimensions. Powder particles are thinly spread on a substrate during the L-PBF process; hence, powder packing properties should influence the molten pool dimensions. This study evaluated the influence of particle size on powder packing properties and molten pool dimensions obtained through numerical simulations. Using particles with different average diameters (<semantics>Dav</semantics>) of 24, 28, 32, 36, and 40 <semantics>μ</semantics>m, a series of discrete-element method (DEM) simulations were performed. The packing fraction obtained from DEM simulations became high as <semantics>Dav</semantics> became small. Several particles piled up for small <semantics>Dav</semantics>, whereas particles spread with almost one-particle diameter thickness for large <semantics>Dav</semantics>. Moreover, the packing structure was inhomogeneous and sparse for large <semantics>Dav</semantics>. As a result of multiphysics computational fluid dynamics (CFD) simulations incorporating particles’ positions as initial solid metal volume, the molten pool width obtained was hardly dependent on the <semantics>Dav</semantics> and was roughly equivalent to the laser spot size used in the simulations. In contrast, the molten pool depth decreased as <semantics>Dav</semantics> decreased. Even if the powder bed thickness is the same, small particles can form a complex packing structure by piling up, resulting in a large specific surface area. This can lead to a complex laser reflection compared to the large particles coated with almost one-particle thickness. The complex reflection absorbs the heat generated by laser irradiation inside the powder bed formed on the substrate. As a result, the depth of the molten pool formed below the substrate is reduced for small particles.